Profile Matching Method In Improving Staff Performance In Asahan University - Irwansyah, Bambang; Harmayani, Harmayani; Apdilah, Dicky (Information Technology and Science (ITScience), 2025)
Asahan University (UNA) is one of the private universities in North Sumatra which has Institution B accreditation in 2024 which is led by the Chancellor Prof. Dr. Tri Harsono, M.Si, in improving quality in the field of administration, UNA always requires staff to give good performance according to their expertise. Objective assessment of job placement will improve performance and motivate staff to perform well. However, the process of placing staff positions at UNA is only based on tenure so that the performance process is less than optimal. Objective: Implementing a system that can provide an assessment of positions in accordance with their expertise. 50 employee data, diploma data, training certificates, work performance, work experience, work period and discipline. Based on the analysis of the process of assigning staff positions to UNA, there are more than 10 staff who have different positions. Furthermore, the data is processed using the profile matching method. The processing stage is through the selection of criteria and then it is processed to get the results of the analysis. Followed by calculating the level of accuracy with the results of the analysis of the UNA staffing section. The results of the testing of this method were that there were 16 staff who were very suitable with their expertise, while 28 people were deemed suitable and 6 more staff were not. So that the level of accuracy is 88%. The assessment of the test results has been able to provide an assessment of the appropriate position. but it can already be recommended to assist the staffing of UNA in analyzing the positions that are currently running to improve the performance of staff in the UNA environment.